Morphology of Middle Cerebral Artery Aneurysms: Impact on Surgical Strategy and on Postoperative Outcome. (27th March 2013) - Schebesch, Karl-Michael; Proescholdt, Martin; Steib, Kathrin; Ullrich, Odo-Winfried; Herbst, Andreas; Rennert, Janine; Brawanski, Alexander
Abstract : The outcome of middle cerebral artery (MCA) aneurysm clipping depends on the presence of subarachnoid hemorrhage (SAH). Moreover, it is influenced by anatomical features of the aneurysm and its parent artery. We hypothesized that morphological characteristics of the aneurysm may be predictive for postoperative outcome. Therefore, we identified radiographic assessable details that predicted the surgical difficulty and the risk for new ischemia. The angiograms of 151 consecutive patients (82 presenting with SAH) were analyzed in a standardized fashion focusing on 12 defined morphological aspects. The results were correlated to intraoperative rupture and to postoperative ischemia. Aneurysms presenting with SAH were associated with irregular shape, larger maximum diameter, and larger dome-to-base distance (DBD) and were located more frequently on the M2 segment. Multivariate analysis revealed 6 independent predictors for intraoperative rupture: SAH, location on M2 segment, DBD, maximum diameter, diameter of the parent MCA, and the presence of branching vessel. Independent predictors of surgery-related ischemia were identified: SAH, irregular shape, location on M2 segment, DBD, and the neck-to-vessel ratio (NVR). In MCA aneurysms, independent predictors for the risk of rupture intraoperatively and for the postsurgical outcome were the presence of SAH, location on the M2-segment, size (DBD), and the broadness of the neck.